2017
DOI: 10.1371/journal.pone.0182786
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the MHC class II in triple-negative breast cancer is associated with tumor-infiltrating lymphocytes and interferon signaling

Abstract: Tumor-infiltrating lymphocytes (TILs) have been known for their strong prognostic and predictive significance in triple-negative breast cancer (TNBC). Several mechanisms for TIL influx in TNBC have been elucidated. Major histocompatibility complex class II (MHC-II) is an essential component of the adaptive immune system and is generally restricted to the surface of antigen-presenting cells. However, it has been reported that interferon-gamma signaling may induce MHC-II in almost all cell types, including those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
79
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(91 citation statements)
references
References 40 publications
6
79
0
1
Order By: Relevance
“…This is noteworthy because T lymphocyte infiltration is associated with good prognosis in breast cancer patients, while the activation of IFN-γ-producing T helper 1 and CD8 + T cells is important for anti-cancer response. 46 The restimulation of splenocytes from BoHV-4-mxCT-vaccinated mice with 4T1 cells also increased the percentage of CD107 + T cells. Nevertheless, only a very slight increase in the ability of splenocytes to kill 4T1 cells in vitro was detected when compared with splenocytes from BoHV-4-A29 control mice.…”
Section: Discussionmentioning
confidence: 94%
“…This is noteworthy because T lymphocyte infiltration is associated with good prognosis in breast cancer patients, while the activation of IFN-γ-producing T helper 1 and CD8 + T cells is important for anti-cancer response. 46 The restimulation of splenocytes from BoHV-4-mxCT-vaccinated mice with 4T1 cells also increased the percentage of CD107 + T cells. Nevertheless, only a very slight increase in the ability of splenocytes to kill 4T1 cells in vitro was detected when compared with splenocytes from BoHV-4-A29 control mice.…”
Section: Discussionmentioning
confidence: 94%
“…9), which are known to be associated with good prognosis in patients with TNBC (10)(11)(12)(13)(14). An independent research team performed IHC on 681 TNBC patient tumors and confirmed that high expression of MHCII in tumor cells was associated with large amounts of tumor-infiltrating CD4-and CD8-positive T cells, and longer DFS (15). Mouse studies have shown that MHCII expression on tumor cells triggers T-cell recruitment and inhibits tumor progression (16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 98%
“…Suppression of cell surface MHC I is a well-documented mechanism used by some tumors to evade the immune system [8]. Conversely, high MHC I expression in triple negative breast tumors is correlated with increased tumor-infiltrating lymphocytes and better prognosis in patients [40]. One important phenotype caused by Pik3ca loss in KPC cells is upregulation of MHC I on the cell surface.…”
Section: Discussionmentioning
confidence: 99%